Implementation of the Six Sigma-DMAIC Method in Improving Quality Product Scanning Units in the Electronics Industry - Dimas Azib Saputra; Hibarkah Kurnia; Syarah Rizkia Feriaty (TEKNOSAINS : Jurnal Sains, Teknologi dan Informatika, 2025)
The current era of globalization demands that all sectors of the manufacturing industry can improve the quality of service to customers. The electronics industry sector in Indonesia still has several defective products received by distributors. One electronic product that still has defects in the product is the scanner unit product. This research aims to identify defects that occur in the scanner unit assembly process and improve product quality by controlling the process. This research method uses the Six Sigma method at the Define, Measure, Analyze, Improve, Control (DMAIC) stages. This research has found that there are dominant foreign material defects of 221 pcs (35.42%) of the total defects of 624 pcs from January to February 2024. The causal factor is that the man consisting of WI (Work Instruction) is not carried out properly and the operator is not careful. at the checkpoint, the method consists of installing the glass label in the glass box, there is no process of checking the glass box before reuse, the material consists of burrs on the lower housing material, the presence of dust and stains on the carriage cis components, and the machine consists of the vacuum device does not inhale optimally, and the air pressure in the blowing machine is not optimal. The results of this research show an improvement in total defects from 624 pcs in Jan - Feb 2024 to 229 pcs and in April - May 2024, with a percentage of 1.662% decreasing to 0.571%. Meanwhile, the sigma level percentage results increased by 0.33 from 4.39 to 4.72 sigma level.